PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI PADA KANTOR SEKRETARIAT DAERAH KABUPATEN KUTAI BARAT - Elisa Pascalia Apriliani (ADMINISTRASI PUBLIK, 2020)
Elisa Pascalia Apriliani, Public Administration Study Program, Department of State Administration, Faculty of Social and Political Sciences, "The Effect of Human Resources Development on Employee Performance at the Regional Secretariat Office of the West Kutai Regency". under the guidance of Ms. Salasiah, S. Sos., M.Si as supervisor I and Mr. Drs. H. Maskan, AF. M. Si as supervisor II.This research is motivated by the influence of human resource development on employee performance at the West Kutai Regency Secretariat Office, so that civil servants / officials at the West Kutai Regency Regional Secretariat have competencies that can be relied on and are of high quality.The purpose of this study was to determine how much influence the development of human resources on the performance of the employees of the Regional Secretariat Office of the West Kutai Regency. The type of research used was quantitative, used to analyze the influence between research variables. The type of data used is questionnaire, observation, interview, and documentation.From the results of research on the analysis of hypothesis calculation data through the t test obtained t arithmetic for human resource development variables of 1,898 where t arithmetic greater than t table (1,898> 1,667), with a significant level of 0.002 <0.05 then Ho is rejected or Ha is accepted , so that partially there is a significant positive effect between human resource development on employee performance. while for R Square obtained 0.740, which means that 74% of employee performance has a positive influence on human resource development.